Validade e reprodutibilidade do teste de marcha estacionária de dois minutos em pacientes com doença arterial periférica - Braghieri, Heloisa Amaral (2019)
Introduction: Patients with peripheral arterial disease (PAD) who present with intermittent claudication (IC) evolve with functional decline and limitations to perform activities of daily living. Although there are specific functional tests for these patients, few are applicable in practical situations, making it necessary to identify tests that can be used in these conditions. Objective: To analyze the validity and reproducibility of the two-minute step test (2MST) in patients with PAD. Methods: Twenty-four patients with PAD and IC symptoms who were recruited at the Nove de Julho University Intermittent Claudication clinic participated in the study. Patients underwent 2MST and the six-minute walk test (6MWT) twice. Before and after the tests, heart rate and blood pressure were obtained. The heart rate response, number of steps until the patient started to feel the pain and the total number of steps in the test were measured. Immediately after, the perception of effort (Borg) was obtained; perception of pleasure and displeasure (Hardly and Rejeski scale), perception of pain (visual analogue scale of pain - Eva). Results: The intraclass correlation coefficients observed between the two 2MST were higher than 0.9 for the performance variables and for the average heart rate. Bias of 0.7 and limits of agreement between 11.24 and -9.60 were observed and the presence of an outlier was observed. The performance of the 2MST test was correlated with the 6MWT (r = 0.25, p = 0.22). Conclusion: 2MST has good reproducibility in patients with symptomatic PAD. However, performance on 2MST is not correlated with the 6MWT. Thus, the use of 2MST is not an accurate test to assess the functional capacity of patients with PAD and symptoms of intermittent claudication, and cannot replace the 6MWT.